Pembangunan Provinsi Aceh: Kebutuhan Sinergitas Dan Pemetaan Ancaman - Heru Syah Putra; Said Fadhil; Edy Saputra (Jurnal Transformasi Administrasi, 2019)
The development challenges in Aceh is increasing in a row of strategic environmental changes, including globalization which bring new challenges of Aceh development. Several social and macro economic indicators shows that frustrating numbers. Poverty is becoming the main problems of development. The Huge fiscal authority has not able to brought improvement which show low level development synergy. Mapping of development threat is becoming more significant for collecting preventive or curative proceeding. This purpose research for mapping the development threat in Aceh province. The result of this research shows that Aceh will deal with four threaten namely politic, economic, social, and information technology. Poverty obtains huge attention while the other side poverty in Aceh still on the high level than the capacity of Aceh fiscal. Number of unemployment is high enough it because of low investment. Furthermore, natural disaster also affects the quality of development and the increasing of drugs trafficking.